Effect of bentonite on benzene vapor adsorption in order to determine the activation conditions of log bentonite - Nazokat, G'aniyeva; Ochilov , Golibjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In the article, the adsorption properties of benzene vapor by adsorbents derived from Logon bentonite, activated through various thermal and chemical methods, were analyzed. The study highlights that chemical activation significantly enhances the adsorption capacity of Logon bentonite (LB-1). The comparison between untreated bentonite and chemically activated forms reveals improved benzene vapor adsorption in the chemically treated bentonite, indicating that the activation process has a substantial impact on the material's adsorption efficiency.